2018
DOI: 10.1016/j.nbd.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Vascular tight junction disruption and angiogenesis in spontaneously hypertensive rat with neuroinflammatory white matter injury

Abstract: Vascular cognitive impairment is a major cause of dementia caused by chronic hypoxia, producing progressive damage to white matter (WM) secondary to blood-brain barrier (BBB) opening and vascular dysfunction. Tight junction proteins (TJPs), which maintain BBB integrity, are lost in acute ischemia. Although angiogenesis is critical for neurovascular remodeling, less is known about its role in chronic hypoxia. To study the impact of TJP degradation and angiogenesis during pathological progression of WM damage, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 73 publications
8
78
0
Order By: Relevance
“…A key event for a compromised BBB is an alteration in claudin-5, a major occlusion protein for brain endothelial barrier. It has been reported that claudin-5 protein expression is changed/reduced in aging brain endothelial cells (Elahy et al, 2015;Yamazaki et al, 2016;Yang et al, 2018). In agreement, the current study showed that claudin-5 mRNA and protein slowly decline over the lifespan in mice and similarly in human brain microvessels.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A key event for a compromised BBB is an alteration in claudin-5, a major occlusion protein for brain endothelial barrier. It has been reported that claudin-5 protein expression is changed/reduced in aging brain endothelial cells (Elahy et al, 2015;Yamazaki et al, 2016;Yang et al, 2018). In agreement, the current study showed that claudin-5 mRNA and protein slowly decline over the lifespan in mice and similarly in human brain microvessels.…”
Section: Discussionsupporting
confidence: 91%
“…claudin-5 and occludin) and uncontrolled increases in vascular permeability (BBB breakdown), to morphologically fragmented or "difficult to detect" alterations in TJ proteins that can cause small but persistent leaks with excessive perivascular build-up of fluid (BBB leakage) (Stamatovic et al, 2016). At the aging BBB, alterations in the TJ proteins claudin-5, ZO-1 and occludin have been reported with fragmented staining and various degrees of total protein loss (Elahy et al, 2015;Kaur et al, 2011;Lee et al, 2012;Yang et al, 2018). A key event for a compromised BBB is an alteration in claudin-5, a major occlusion protein for brain endothelial barrier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have indicated that WMHs are associated with the cognitive impairment in CSVD [4,[29][30][31], and our results (Fig. 3D, E) are consistant with these findings.…”
Section: Discussionsupporting
confidence: 93%
“…Structural and functional impairment of the BBB, characterized by disruption of endothelial cell-associated connections, is one of the hallmarks of neurologic disease (36), whereas the severity of BBB disruption has been shown to correlate positively with the severity of IS (37)(38)(39). Our study also found that anti-IL-9 mAb improves the destruction of the BBB after stroke and that its mechanism is related to active repair of the damaged TJPs in brain tissue, which is different from the effects of anti-IL-9 mAb on inflammatory diseases of the CNS.…”
Section: Discussionmentioning
confidence: 99%